EKSISTENSI KOMUNITAS DAN AJARAN SYIAH (AHLUL BAIT INDONESIA) DI KALIMANTAN SELATAN - Wahyudin; Mahyuddin Barni; Fajrul Ilmi (Adisam Publisher, 2026)
The purpose of this research is to determine (1) the background of the existence of Shiism in South Kalimantan; (2) the existence of the Shia community in South Kalimantan from the aspects of organization and secretariat; (3) the figures of the Shia movement in South Kalimantan; (4) the focus or emphasis of the Shia movement in South Kalimantan; (5) the Shia theology implanted and developed in South Kalimantan; (6) prominent fiqhi distinctions of the Shia community in South Kalimantan; (7) religious traditions with theological dimensions of Shiism developed in South Kalimantan; and (8) supporting factors for the assimilation of Shia teachings in the South Kalimantan community as well as the phenomena of integration and conflict. The research was conducted using a qualitative approach and descriptive methods. Data were collected through in-depth interviews and literature reviews. The research locations were in the city of Banjarmasin, Banjar regency, and Tanah Bumbu regency. The research informants consisted of Shia figures (ABI officials) and experts on Shiaism. Data analysis was performed using descriptive-qualitative techniques. The results of the research are as follows: 1. The existence of Shiism in South Kalimantan began around the 1980s. The doctrine of Shia entered South Kalimantan through two channels: through trade routes by Arab traders descended from the Ahlul Bait, and through intellectual networks of higher education institutions; 2. The Shia community in South Kalimantan is generally affiliated with the Ahlul Bait Indonesia (ABI) organization in South Kalimantan, established since 2005; 3. Figures of the Shia movement in South Kalimantan, besides Sayyid Abdullah Al-Habsyi as the leader of the wilyah, also include Musa Al-Mawardi in Martapura, Habib Baghir Assegaf in Banjarbaru, and Habib Ali bin Muhammad bin Sholeh Al-Habsyi from Barabai currently residing in Martapura; 4. The ABI movement in South Kalimantan is currently focused on the cultivation and enhancement of knowledge about monotheism and the Ahlul Bait; 5. Some theological teachings of Shiism embraced and believed by the Shia community in South Kalimantan include Wisyayah, Imamah, ‘Ishmah, Raj’ah, Taqiah, Wilayah, ‘Adl, Sunnah, Ghaybah, Syafaat, Ijtihad, Do’a, and Taqlid; 6. From a fiqh aspect, some differences observed with Sunni include: the practice of combining (jama’) prayers to alleviate difficulties in performance, prostration on dry earth that has been imprinted and pure (called turbah) used as a prostration base in prayers, not folding hands during standing position in prayer as done by Sunnis, breaking the fast during Ramadan for travelers, and regarding the consumption of living animals in water, especially fish, they prohibit scaleless fish (catfish, carp, etc.); 7. Religious traditions with theological dimensions in fostering love for the Ahlul Bait practiced by the Shia community in South Kalimantan include commemorating the day of Ashura, the Arbaeen commemoration, visiting the graves of the Prophet and the Holy Imams, commemorating the birth (milad) and death (haul) anniversaries of the Imams and scholars, and celebrating Eid al-Ghadir; 8. The existence and development of Shiism in South Kalimantan generally do not provoke sharp conflicts in Kalimantan society, only causing resistance from certain parties temporarily.